2022
DOI: 10.3390/molecules27217404
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Preparation of Soft Rock Similar Materials Using Redispersible Latex Powder as a Modifier

Abstract: The engineering geological problems of soft rock are common in large slope engineering and underground engineering surrounding rock. In order to study the change in mechanical properties of soft rock under the action of loading, excavation and rainfall, this paper carried out experimental research on similar materials of soft rock. The similar material of soft rock is prepared by using iron fine powder, barite powder and quartz sand as aggregate, gypsum as binder and redispersible latex powder as regulator. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…In regression analysis, it was found that the elastic modulus of similar mudstone materials in the above mix proportions is slightly higher than the requirements in Table 14 . Based on the regulatory effect of re-dispersible latex powder on elastic modulus in the reference 10 , a re-dispersible latex powder with a cement content of 6% was added to the mudstone ratio to obtain the final ratio.…”
Section: Materials Preparation and Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In regression analysis, it was found that the elastic modulus of similar mudstone materials in the above mix proportions is slightly higher than the requirements in Table 14 . Based on the regulatory effect of re-dispersible latex powder on elastic modulus in the reference 10 , a re-dispersible latex powder with a cement content of 6% was added to the mudstone ratio to obtain the final ratio.…”
Section: Materials Preparation and Applicationmentioning
confidence: 99%
“…Lei Zhongdai et al 9 conducted sensitivity analyses on the density, cohesion, compressive8 strength, and other indexes of similar materials through orthogonal experiments. Ren Xu et al 10 found that similar materials bonded with gypsum should be cured for at least 7 days or cured to constant weight. In addition, some scholars have used laundry detergent and hydraulic oil to simulate the viscosity of rocks 11 – 13 .…”
Section: Introductionmentioning
confidence: 99%